The Influence of TikTok Media Exposure on Body Image and Self-Esteem in Adolescents - Mita Yunani; Ika Ariyati; Kus Hendar; Faridah Pardi; Emi Puspita Dewi; Nera Leiya Maisuri (Scidac Plus, 2025)
TikTok is among the most widely used social media platforms by adolescents, featuring unique elements such as algorithm-driven short videos and appearance enhancing filters that differentiate it from other platforms. These characteristics render TikTok particularly influential in shaping adolescents’ perceptions of body image and self-esteem. This study aims to examine the impact of TikTok media exposure on body image and self-esteem among adolescents aged 15 to 18 years. A quantitative method was employed using multivariate linear regression analysis. The sample comprised 172 active TikTok users from Taruna Gajah Mada High School, Metro, Indonesia, with data collected through an online questionnaire. The instruments used included the Media and Technology Usage and Attitudes Scale (MTUAS), the Body Image Scale, and the Rosenberg Self-Esteem Scale. The results revealed that TikTok exposure significantly affected body image (F = 98.697; p < 0.001) and self-esteem (F = 110.177; p < 0.001), with a combined explained variance of 31.3%. Exposure to idealized body-related content fosters social comparison, adversely impacting adolescents’ self-image and confidence. This study underscores the importance of digital literacy and psychosocial support in encouraging healthy social media use among adolescents. It concludes that TikTok exposure plays a substantial role in shaping how adolescents perceive their bodies and assess their self-worth, highlighting the media’s influence on self-concept and psychological well-being.